Carbonyl‐β‐Cyclodextrin as a Novel Binder for Sulfur Composite Cathodes in Rechargeable Lithium Batteries. (4th October 2012) - Wang, Jiulin; Yao, Zhendong; Monroe, Charles W.; Yang, Jun; Nuli, Yanna
Abstract As one of the essential components in electrodes, the binder affects the performance of a rechargeable battery. By modifying β‐cyclodextrin (β‐CD), an appropriate binder for sulfur composite cathodes is identified. Through a partial oxidation reaction in H2O2 solution, β‐CD is successfully modified to carbonyl‐β‐cyclodextrin (C‐β‐CD), which exhibits a water solubility ca. 100 times that of β‐CD at room temperature. C‐β‐CD possesses the typical properties of an aqueous binder: strong bonding strength, high solubility in water, moderate viscosity, and wide electrochemical windows. Sulfur composite cathodes with C‐β‐CD as the binder demonstrate a high reversible capacity of 694.2 mA h g(composite)−1 and 1542.7 mA h g(sulfur)−1, with a sulfur utilization approaching 92.2%. The discharge capacity remains at 1456 mA h g(sulfur)−1 after 50 cycles, which is much higher than that of the cathode with unmodified β‐CD as binder. Combined with its low cost and environmental benignity, C‐β‐CD is a promising binder for sulfur cathodes in rechargeable lithium batteries with high electrochemical performance.